Letter regarding NOBCChE's testimony to the United States Senate, 1976 - National Organization for Black Chemists and Chemical Engineers (1976)
A letter by Maerean Bohannon, editor of the NOBCChE newsletter, requesting that recipients write to three United States senators to express support for William Jackson's, treasurer of the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers (NOBCChE), testimony to the Senate Subcommittee on the National Science Foundation's (NSF) fiscal year 1977 budget. A summary of Dr. Jackson's testimony is included.
Keywords: National Organization for Black Chemists and Chemical Engineers; Jackson, William M., 1936-; National Science Foundation (U.S.); Minority engineers; Minority scientists; Scientists, Black; African American scientists; African American engineers; Chemical engineers; National Science Foundation (U.S.); Bohannon, Maerean